2019
DOI: 10.14742/ajet.5521
|View full text |Cite
|
Sign up to set email alerts
|

Digital equity and accessible MOOCs: Accessibility evaluations of mobile MOOCs for learners with visual impairments

Abstract: Despite the popular claim that massive open online courses (MOOCs) can democratise educational opportunities, this study suggests that current MOOC platforms are not designed to be accessible and inclusive for learners with disabilities. Our main goals in this study were to identify the needs and barriers that learners with visual impairments face when learning with mobile devices in MOOCs and to make recommendations for designing MOOCs that are more accessible and inclusive. We conducted this study in two pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…Despite attention to OER and OER-enabled pedagogy, studies have rarely investigated how existing OER and open educational practices can embrace learners with disabilities and how they can promote their interactions. In terms of digital equity, research has failed to identify clearly the contextual challenges that learners with disabilities face when using OER (Park et al, 2019;Willems & Bossu, 2012). Considering such challenges, we noticed a possible discrepancy between OER designs and learners' disabilities, which may interrupt the expansion of OER-enabled pedagogy for learners with disabilities.…”
Section: Oer In the 21st Centurymentioning
confidence: 90%
See 2 more Smart Citations
“…Despite attention to OER and OER-enabled pedagogy, studies have rarely investigated how existing OER and open educational practices can embrace learners with disabilities and how they can promote their interactions. In terms of digital equity, research has failed to identify clearly the contextual challenges that learners with disabilities face when using OER (Park et al, 2019;Willems & Bossu, 2012). Considering such challenges, we noticed a possible discrepancy between OER designs and learners' disabilities, which may interrupt the expansion of OER-enabled pedagogy for learners with disabilities.…”
Section: Oer In the 21st Centurymentioning
confidence: 90%
“…OER include various types of educational materials for teaching, learning, or assessment, such as textbooks and digital toolkits that consider human modalities (e.g., video and narrations). Since OER focus on the openness of learning resources, OER can contribute to digital equity (Park et al, 2019). Digital equity indicates that each learner has an equal opportunity to access and experience learning resources without physical constraints (Solomon, 2002).…”
Section: Oer In the 21st Centurymentioning
confidence: 99%
See 1 more Smart Citation
“…The research focuses on the potential of these tools to gain insight into the relationships between learning and teaching (e.g. (Brooker et al, 2018;Thompson et al, 2013), examining the impact of MOOCS on accessibility (Park et al, 2019), learning analytics for students (Kitto et al, 2017), and implementation in classrooms (Prieto et al, 2019). Best practice and the influence of video for education is still under discussion (Fyfield et al, 2019).…”
Section: Educational Technology 2010-2020mentioning
confidence: 99%
“…Law et al (2013) reported that substantial numbers of learners with accessibility needs are using open educational resources (OER) and MOOCs. However, there is limited research on how MOOCs are designed to consider accessibility and the diverse needs of their learners (Ingavélez-Guerra et al, 2020;Park et al, 2019;Sanchez-Gordon & Luján-Mora, 2017;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%